Antipsychotic Overdosing and Polypharmacy in Schizophrenic Delinquents Explored - Günther, M. P. (International journal of offender therapy and comparative criminology, 2020)
A logistic regression model for 289 cases of schizophrenic offenders in a Swiss forensic hospital between 1995 and 2016 revealed the following factors for above average levels of antipsychotic overdosing and polypharmacy: Odds for overdosing increased in absence of a personality disorder (237%), for each point increase in emotional withdrawal (63.5%) and motor retardation (71.7%), and decreased for poor rapport (42.3%) recorded at admission. Odds for polypharmacy increased with complaints about physicians (157%), for each point increase in IQ (3.6%; range = 65-131, M = 92, SD = 14), reduction of the security level of the ward (36.8%; four levels), and for each point increase in poor attention (27.6%) at admission. It decreased with each previous conviction (10.9%; range = 1-21, M = 3, SD = 2), breaking of rules (46.4%) and the administration of compulsory measures (55.7%) on the ward, a poor legal prognosis (29.4%, four levels), and each point increase in grandiosity (40.3%), passive social withdrawal (42.3%), and depressive symptoms (38.7%) at admission.